The fruit borer and the cacao stem (Carmenta theobromae, Lepidoptera: Sesiidae) in the Zarumilla valley, Tumbes, Peru. (2020)
Since 2009, the presence of a pest insect of an unidentified species whose larvae pierce the stems and fruits of the cocoa plant, affecting the commercial value of the fruits by the invasion of secondary pathogenic microorganisms, has been demonstrated in the cocoa plantations of the Zarumilla valley, (Tumbes, Peru). This research work was carried out from March to August 2014 in order to identify and morphologically characterize the borer of the fruit and stem of the cocoa plant not reported for the conditions of this valley. The collections were made in cocoa fields of the Zarumilla valley and the breeding of immature states was carried out in the Entomology laboratory of the National University of Tumbes. The results made it possible to determine that the species whose larva pierces the cacao stems and fruits is Carmenta theobromae. The main morphological characteristics of this species are described, referring to the egg, larva, pupa and adult stages of both sexes. In addition, from the biological material collected in the field during the sampling, it was possible to identify two parasitoids at the family level, a dipteran Tachinidae recovered from larvae and a hymenopteran Chalcididae recovered from pupae. It is concluded that the species that burrows cocoa fruits in cocoa plantations in the Zarumilla Valley is C. theobromae. The present study will serve as the basis for biology and behavioral studies of in relation to environmental factors and to determine if this species has a preference for certain cocoa clones planted in the valley.